Exploring the diversity and pathogenicity of Talaromyces species isolated from clinical in Southern China - Liao, Liuwei; Pan, Kaisu; Zheng, Dongyan; Wang, Shuangjie; Wu, Weixuan; Cao, Cunwei (Frontiers in Microbiology, 2025)
In recent years, some species of Talaromyces have emerged as human pathogens but rarely reported from Southern China, the endemic region of Talaromyces marneffei. To investigate the diversity of Talaromyces species in Southern China, we collected 59 clinical Talaromyces isolates, which were identified as 11 different species through molecular analysis. Notably, several species exhibited phenotypic characteristics similar to T. marneffei, such as red pigment production at 25°C and monoverticillate or biverticillate conidiophores with globose to subglobose conidia, potentially leading to misidentification. Antifungal susceptibility testing revealed distinct drug susceptibility profiles between T. marneffei and other species. Furthermore, seven species demonstrated growth at 37°C and induced inflammatory lung damage in mice, suggesting their pathogenic potential. These emerging Talaromyces pathogens were primarily isolated from respiratory tract samples of immunocompromised patients. Our findings highlight the rich diversity of Talaromyces species clinically in Southern China, emphasizing the critical importance of considering their potentially pathogenic.